Removal of systematic seasonal atmospheric signal from interferometric synthetic aperture radar ground deformation time series. Issue 17 (10th September 2014) - Samsonov, Sergey V.; Trishchenko, Alexander P.; Tiampo, Kristy; González, Pablo J.; Zhang, Yu; Fernández, José
Abstract Applying the Multidimensional Small Baseline Subset interferometric synthetic aperture radar algorithm to about 1500 Envisat and RADARSAT‐2 interferograms spanning 2003–2013, we computed time series of ground deformation over Naples Bay Area in Italy. Two active volcanoes, Vesuvius and Campi Flegrei, are located in this area in close proximity to the densely populated city of Naples. For the first time, and with remarkable clarity, we observed decade‐long elevation‐dependent seasonal oscillations of the vertical displacement component with a peak‐to‐peak amplitude of up to 3.0 cm, substantially larger than the long‐term deformation rate (<0.6 cm/yr). Analysis, utilizing surface weather and radiosonde data, linked observed oscillations with seasonal fluctuations of water vapor, air pressure, and temperature in the lower troposphere. The modeled correction is in a good agreement with observed results. The mean, absolute, and RMS differences are 0.014 cm, 0.073 cm, and 0.087 cm, respectively. Atmospherically corrected time series confirmed continuing subsidence at Vesuvius previously observed by geodetic techniques.